Solid electrolyte and preparation method thereof
By doping low-cost elements to form a low eutectic phase, the problems of unstable LLZO electrolyte at room temperature and high sintering temperature are solved, and a solid electrolyte with high ionic conductivity and low cost are achieved, which is suitable for solid-state lithium-ion batteries.
Patent Information
- Application Number
- CN202311348630.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-25
AI Technical Summary
Among the existing solid-state lithium-ion batteries, the garnet-type Li7La3Zr2O12 (LLZO) electrolyte has two crystal structures: cubic phase and tetragonal phase at room temperature. The ionic conductivity of the cubic phase is high but unstable, and the sintering temperature and time of the ceramic electrolyte are high, which increases production cost and energy consumption.
By doping low-cost elements such as Ga, Al, W, Ta, etc., a low eutectic phase is formed, the sintering temperature and time of the ceramic sheet are reduced, and the Li vacancy is introduced to stabilize the structure of the cubic phase LLZO.
A cubic phase LLZO that is stable at room temperature is achieved, reducing the sintering temperature and time, reducing production costs, and improving the density and ionic conductivity of the solid electrolyte.
Smart Images

Figure CN119890419A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid electrolyte and a preparation method thereof, and a solid lithium ion battery comprising the solid electrolyte. Background Art
[0002] Lithium-ion batteries have been widely used due to their high energy density, low self-discharge, environmental friendliness and no memory effect. However, due to the organic electrolytes used in existing commercial lithium-ion batteries, the batteries have serious safety issues such as flammability and explosion. All-solid-state batteries using solid electrolytes do not contain flammable components and can use lithium metal as the negative electrode, which greatly improves the safety and energy density of lithium-ion batteries, making all-solid-state batteries a research focus in recent years.
[0003] Garnet-type lithium lanthanum zirconium oxide Li7La3Zr2O 12 (LLZO) electrolyte has the characteristics of high ionic conductivity, good thermal stability, high electrochemical window and stability to lithium metal, making it one of the most promising solid electrolytes. However, at room temperature, LLZO has two crystal structures with large differences in ionic conductivity. The ionic conductivity of the cubic phase (~10 -4 S / cm) than the tetragonal phase (~10 -6 S / cm) is about two orders of magnitude higher, so it is necessary to avoid the transformation of LLZO from the cubic phase to the tetragonal phase during the production and use of the electrolyte. Studies have reported that the cubic phase of LLZO at room temperature can be stabilized by doping with high-priced elements such as Nb, Ga, Ta, Ce, etc., so as to improve the ionic conductivity of LLZO. However, these metal elements are expensive and not conducive to practical applications, and the manufacture of ceramic solid electrolytes requires long-term sintering at temperatures above 1200°C, which further increases time and energy costs. In addition, the known doping elements cannot introduce more lithium vacancies in the crystal phase, and the improvement of the ionic conductivity of LLZO is limited.
[0004] Therefore, a technology is needed that can form a eutectic phase by doping low-cost elements to reduce the sintering temperature and time of the ceramic sheet and introduce Li vacancies. Summary of the invention
[0005] The present invention aims to solve the above-mentioned problems in the prior art. That is, the purpose of the present invention is to provide a solid electrolyte that forms a low-melting phase by doping low-cost elements, thereby reducing the sintering temperature and time of the solid electrolyte ceramic sheet and introducing Li vacancies. The purpose of the present invention is also to provide a method for preparing the solid electrolyte, and a lithium ion battery using the solid electrolyte.
[0006] The first aspect of the present invention provides a solid electrolyte represented by Formula 1,
[0007] Li 7-mx-(n-4)y A x La3Zr 2-y B y O 12 Formula 1,
[0008] wherein A is one or more elements selected from Ga, Al, and Zn,
[0009] B is one or more elements selected from W, Ta, Nb, and Sb,
[0010] 0 < x ≤ 1, 0 < y ≤ 1, and 7 - mx - (n - 4)y ≥ 6, where m is the valence state of A present in the solid electrolyte, which is 2 or 3, and n is the valence state of B present in the solid electrolyte, which is 5 or 6.
[0011] In some specific embodiments, in Formula 1, A is Ga or Al, and m is 3. In some specific embodiments, in Formula 1, B is W or Ta, and n is 5 or 6.
[0012] In some preferred embodiments, in Formula 1, A is Ga and m is 3. In some preferred embodiments, in Formula 1, A is Al and m is 3. In some preferred embodiments, in Formula 1, B is W and n is 6. In some preferred embodiments, in Formula 1, B is Ta and n is 5. In some preferred embodiments, in Formula 1, 0.02 ≤ x ≤ 1. In some preferred embodiments, in Formula 1, 0.02 ≤ y ≤ 1. More preferably, 0.02 ≤ x ≤ 0.2 and 0.02 ≤ y ≤ 0.2.
[0013] The second aspect of the present invention provides a method for preparing the solid electrolyte of the first aspect of the present invention, and the preparation method includes the following steps:
[0014] (1) Mix the precursors of each element with a solvent and then perform ball milling, followed by drying;
[0015] (2) Pre - sinter the mixture obtained in step (1), then mix it with the solvent again and perform ball milling, followed by drying;
[0016] (3) Mold the mixture obtained in step (2);
[0017] (4) Sinter the molded body obtained in step (3) to obtain a solid electrolyte.
[0018] In some specific embodiments, in step (1), the molar content of the lithium source is 5% - 20% in excess relative to the lithium element in the solid electrolyte, preferably 10% - 15%.
[0019] In some specific embodiments, in step (2), the pre-calcination temperature is 700-1100°C, preferably 750-900°C.
[0020] In some specific embodiments, in step (3), the forming is performed by cold pressing.
[0021] In some specific embodiments, in step (4), the sintering conditions include: a heating rate of 5 to 20°C / min, and / or a sintering temperature of 1000 to 1500°C, preferably 1000 to 1200°C, more preferably 1050 to 1150°C, and / or a sintering time of 0.1 to 24 hours.
[0022] The third aspect of the present invention provides the use of the solid electrolyte of the first aspect of the present invention or the solid electrolyte obtained by the preparation method of the second aspect of the present invention in a solid-state lithium-ion battery.
[0023] A fourth aspect of the present invention provides a lithium-ion battery, which includes the solid electrolyte of the first aspect of the present invention or the solid electrolyte obtained by the preparation method of the second aspect of the present invention.
[0024] The beneficial effects of the invention include:
[0025] In the solid electrolyte of the present invention, the use of precious metals is reduced by co-doping LLZO with low-cost metal elements such as W, thereby reducing costs. At the same time, the doping of elements such as W can replace the Zr position of the cubic phase crystal form of LLZO, stabilize the cubic phase, and introduce more Li vacancies in LLZO.
[0026] Specifically, among the tetragonal phase (space group is I41 / acd) and the cubic phase (space groups are Ia-3d and I-43d), the cubic phase LLZO with space group I-43d is a fast ion conductor, and its lithium ion conductivity is 2 orders of magnitude higher than that of the tetragonal phase LLZO. This is because the cubic phase LLZO has uniformly distributed lithium ion diffusion channels in the three directions of a, b, and c, while the tetragonal phase LLZO only has two-dimensional lithium ion diffusion channels in the two directions of a and b. However, the cubic phase LLZO is not stable at room temperature. In order to enhance the stability of the LLZO cubic phase, the present invention adopts a method of doping with high-valent metal cations to introduce W into the LLZO lattice. 6+ 、 5+ , Nb 5+ , Ga 3+ The addition of metal cations increases the lithium ion vacancies, decreases the Li site occupancy, increases the entropy of the system and decreases the free energy, thus obtaining a cubic phase LLZO that can exist stably at room temperature.
[0027] In addition, the doping of elements such as W also helps to form a low-melting point phase at the grain boundary, reduce the sintering temperature, promote the densification of ceramics, and improve the ionic conductivity of ceramic sheets after sintering. The high ionic conductivity of solid electrolytes can support high-rate charging and discharging of solid-state batteries and reduce the charging and discharging time of batteries. The high ionic conductivity of solid electrolytes can also reduce the internal resistance of batteries and reduce battery polarization. In addition, high-density solid electrolytes have higher ionic conductivity because they have more continuous ion pathways. At the same time, high-density solid electrolytes have fewer macroscopic defects (pores) and higher mechanical properties, which can inhibit the piercing of lithium dendrites.
[0028] In addition, during the sintering process of the co-doped LLZO, the doping elements are enriched at the grain boundaries of the solid electrolyte and can also form a low-melting point phase at the grain boundaries, reducing the temperature required for sintering, thereby reducing the sintering temperature and time of the solid electrolyte ceramic sheet, further reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Comparison of the sintered ceramic sheets of Example 1 and Comparative Example 1.
[0030] Figure 2 1 and 2 are XRD diagrams of the solid electrolytes of Example 1 and Comparative Example 1 of the present invention.
[0031] Figure 3 This is the impedance spectrum of the solid electrolyte of Example 1 of the present invention.
[0032] Figure 4 This is a SEM image of the solid electrolyte of Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The present invention will be further described below by specific embodiments. Unless otherwise specified, the terms used herein have the same meaning as those of ordinary skill in the art generally understand. The numerical limits or ranges stated herein include endpoints, specifically all values and subranges within the numerical limits or ranges.
[0034] In the present invention, unless otherwise specified, the letter B refers to the doping element used in the solid electrolyte, rather than specifically the chemical element boron.
[0035] The first aspect of the present invention provides a solid electrolyte represented by Formula 1,
[0036] Li 7-mx-(n-4)y A x LqCy 2-y B y O 12 Formula 1.
[0037] In some specific embodiments of the present invention, in the solid electrolyte shown in Formula 1, the doping element A can be one or more elements selected from Ga, Al and Zn. Through the doping of these elements, lithium vacancies can be created in the solid electrolyte lattice, and the lattice constant can be increased, and the lithium ion migration barrier can be reduced, thereby improving the ionic conductivity of the solid electrolyte. Considering the reasons such as the efficiency of improving the ionic conductivity of the solid electrolyte after doping, the doping element A is preferably Ga or Al, and more preferably Ga.
[0038] In some specific embodiments of the present invention, in the solid electrolyte shown in Formula 1, the doping element B can be one or more elements selected from W, Ta, Nb and Sb. Through the doping of these elements, the Zr position can be replaced, and due to the high valence state of the doping element, the concentration of lithium vacancies is increased. At the same time, the doping element can be enriched at the grain boundary of the solid electrolyte to form a low eutectic phase, reduce the temperature required for sintering, and increase the density of the solid electrolyte after sintering. Considering the reasons such as the improvement of the ionic conductivity of the solid electrolyte after doping and the efficiency of reducing the sintering temperature, the doping element B is preferably W or Ta, and more preferably W.
[0039] In some specific embodiments of the present invention, in Formula 1, m is the valence state of A in the solid electrolyte, which is 2 or 3, and n is the valence state of B in the solid electrolyte, which is 5 or 6. For example, when the doping element at the A position is Ga or Al, m is 3; when the doping element at the A position is Zn, m is 2. Similarly, when the doping element at the B position is W, n is 6; when the doping element at the B position is Ta, n is 5; when the doping element at the B position is Nb, n is 5; when the doping element at the B position is Sb, n is 5.
[0040] In some specific embodiments of the present invention, in the solid electrolyte shown in Formula 1, the parameters x and y representing the doping amounts of elements A and B, respectively, independently represent values greater than 0 and less than or equal to 1. When the doping amount of element A exceeds 1, the crystal structure of the solid electrolyte will change; on the other hand, when the doping amount of element B exceeds 1, impurities will be generated in the material, and the ionic conductivity of the solid electrolyte will be seriously reduced.
[0041] In some specific embodiments of the present invention, preferably, x and y are each a value greater than 0 and less than 1, more preferably, x and y are each a value between 0.02 and 1, that is, 0.02≤x≤1, 0.02≤y≤1; further preferably, 0.02≤x≤0.2, 0.02≤y≤0.2.
[0042] According to the present invention, x and y may each independently be 0.02, 0.05, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.
[0043] In some specific embodiments of the present invention, preferably, the lithium content in the solid electrolyte shown in Formula 1 is 6.0 to 6.9, that is, 6.0≤7-mx-(n-4)y≤6.9, more preferably 6.2 to 6.8, and most preferably 6.3 to 6.6. According to theoretical calculations, for the doped garnet-type LLZO electrolyte, the LLZO ion conductivity is the highest when the Li content is maintained at 6.3 to 6.6.
[0044] The second aspect of the present invention provides a method for preparing a solid electrolyte represented by Formula 1, the preparation method comprising the following steps:
[0045] (1) Precursors of each element (Li, A, La, Zr and B) are mixed with a solvent, ball-milled and then dried;
[0046] (2) pre-calcining the mixture obtained in step (1), then mixing it with a solvent again, ball milling it, and then drying it;
[0047] (3) forming the mixture obtained in step (2);
[0048] (4) Sintering the molded body obtained in step (3) to obtain a solid electrolyte.
[0049] In some specific embodiments of the present invention, the precursor of each element in the solid electrolyte represented by Formula 1 may be an oxide, hydroxide or salt (e.g., nitrate) of the corresponding element. For example, as a lithium source, lithium hydroxide monohydrate (LiOH·H2O) may be used; as a lanthanum source, La2O3 may be used; as a zirconium source, ZrO2 may be used. In addition, as a gallium source, gallium oxide (Ga2O3) may be used; as an aluminum source, aluminum oxide (Al2O3) may be used; as a tungsten source, tungsten oxide (WO3) may be used; as a tantalum source, tantalum oxide (Ta2O5) may be used. The precursor may be pretreated according to actual conditions. For example, when La2O3 is used, it is necessary to calcine at above 900°C for more than 12 hours in advance to remove moisture.
[0050] In some specific embodiments of the present invention, in step (1), the precursors of each element can be weighed with reference to the stoichiometric ratio of the final product and placed in a zirconia tank, and a solvent and zirconia balls are added for ball milling. The mixed powder after uniform mixing is placed in a blast oven for heating and drying to completely remove the solvent. Subsequently, in step (2), the dried mixed powder obtained in step (1) is pre-calcined, and then the pre-calcined powder is placed in a zirconia tank again, and the solvent and zirconia balls are added and ball milled there, and the powder after ball milling is placed in a blast oven for drying to completely remove the solvent. In step (3), a certain amount of the powder obtained in step (2) is weighed and placed in a mold for molding to obtain a molded body. Finally, in step (4), after the molded body in step (3) is sintered and cooled, the element-doped garnet-type solid electrolyte of the present invention is obtained.
[0051] Since the lithium in the mixture will volatilize at high temperatures, in order to obtain a solid electrolyte with a desired stoichiometric ratio, it is preferred that a portion of excess lithium is included in the mixture to be sintered. The inventors have confirmed through experiments that a small amount of excess lithium will not affect the physical structure of the solid electrolyte. On the one hand, the excess proportion of lithium during the sintering process is small, which can just offset the amount of lithium volatilization. On the other hand, a small amount of lithium residue can form a lithium-rich phase at the grain boundary, such as lithium oxide (Li2O), lithium zirconium oxide (Li2ZrO3), etc., so that the element-doped LLZO grains are better connected and the compactness after sintering is increased. In addition, in the present invention, the chemical formula of the solid electrolyte refers to the chemical composition of the main crystalline phase structure of the solid electrolyte. A small amount of other crystalline phases and / or impurities present in the macroscopic solid electrolyte product should not be understood as changing the chemical composition of the solid electrolyte.
[0052] In some specific embodiments, preferably, in step (1), the lithium source is 5% to 20% in excess of the molar content of Li in the target product, preferably 10% to 15% in excess, and more preferably 10% in excess. For example, the excess ratio of the lithium source can be calculated based on the feed ratio of other element precursors, that is, based on the amount of La, Zr or doping elements A, B, the molar content of Li in the product is calculated according to the chemical formula of the solid electrolyte, and then the corresponding molar ratio is increased to use as the precursor of the lithium element in step (1).
[0053] In addition, in step (1), the mass ratio of the precursor to the solvent can be 1:1-5, the ball-to-material ratio can be 1:1-10, the ball mill speed can be 100-800 rpm, the ball milling time can be 1-24 hours, the drying temperature can be 50-200° C., and the drying time can be 2-24 hours. In addition, the solvent can be isopropanol.
[0054] In some specific embodiments, in step (2), the pre-calcination temperature may be 700-1100° C., preferably 750-900° C. The pre-calcination temperature may be 1-24 hours, the mass ratio of the mixture to the solvent may be 1:1-5, the ball-to-material ratio may be 1:1-10, the ball mill speed may be 100-800 rpm, the ball milling time may be 1-24 hours, the drying temperature may be 50-200° C., and the drying time may be 2-24 hours. In addition, the solvent may be isopropanol.
[0055] In some specific embodiments, in step (3), the powder obtained in step (2) is sieved and weighed to obtain a certain amount, which is then cold-pressed in a circular mold to obtain a circular disc as a molded body.
[0056] In some specific embodiments, in step (4), the sintering conditions may include: a heating rate of 5 to 20° C. / min, and / or a sintering temperature of 1000 to 1500° C. In order to reduce energy consumption during the sintering process, the sintering temperature is preferably 1000 to 1200° C., more preferably 1050 to 1150° C. In addition, the sintering time may be 0.1 to 24 hours, preferably 3 to 15 hours.
[0057] The third aspect of the present invention provides the use of the solid electrolyte of the first aspect of the present invention or the solid electrolyte obtained by the preparation method of the second aspect of the present invention in a solid-state lithium-ion battery.
[0058] A fourth aspect of the present invention provides a lithium ion battery. In some specific embodiments, the lithium ion battery of the present invention comprises the solid electrolyte of the first aspect of the present invention or the solid electrolyte obtained by the preparation method of the second aspect of the present invention. There is no particular limitation on the materials and preparation methods of other parts of the lithium ion battery except the solid electrolyte, and conventional materials and preparation methods in the art can be used.
[0059] Example
[0060] The present invention is described in detail below by way of examples, which are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified. The various reagents and equipment used in the following examples are all commercially available products, and there are no special requirements.
[0061] Example 1Li 6.5 Ga 0.1 LqCy 1.9 W 0.1 O 12 Preparation and characterization of
[0062] According to the stoichiometric ratio of the final product and the lithium source excess of 10%, 3.000g of lithium hydroxide monohydrate (LiOH·H2O), 0.0937g of gallium oxide (Ga2O3), 4.89g of lanthanum oxide (La2O3), 2.337g of zirconium oxide (ZrO2) and 0.2318g of tungsten oxide (WO3) were weighed and put into a zirconium oxide tank, and then 20g of isopropanol and 30g of zirconium oxide balls were added, and ball milled at 500rpm for 10h, and mixed evenly to obtain a mixed powder. Then the mixed powder was placed in a blast oven and dried at 70°C for 12h to completely remove the solvent isopropanol.
[0063] Then pre-sinter at 900°C for 12h, then put the pre-sintered powder into a zirconia pot, add 20g isopropanol and 30g zirconia balls, and mill at 500rpm for 10h to mix evenly to obtain a mixed powder. Then put the mixed powder into a blast oven and dry it at 70°C for 12h to completely remove the solvent isopropanol.
[0064] 1.5 g of the dried material was weighed and placed in a circular mold with a diameter of 15 mm, and the mold was pressed at room temperature and a pressure of 200 MPa for 5 minutes to obtain a circular disc.
[0065] The formed disc was heated to 1100°C at a heating rate of 10°C / min, kept at this temperature for 12 hours and then cooled naturally to obtain a Ga and W co-doped garnet solid electrolyte ceramic sheet with a chemical formula of Li 6.5 Ga 0.1 LqCy 1.9 W 0.1 O 12 .
[0066] The sintered ceramic sheet is Figure 1 As shown. 6.5 Ga 0.1 LqCy 1.9 W 0.1 O 12 The ceramic sheet was characterized by the following method to obtain its XRD spectrum, impedance spectrum, SEM image, ionic conductivity and density data.
[0067] The XRD test instrument was a Japanese Rigaku MiniFlex, with a scanning angle of 10-60° and a scanning rate of 8° / min.
[0068] The SEM testing instrument is Zeiss Sigma 300, which is used to directly test the sintered solid electrolyte.
[0069] The impedance test process is as follows: the sintered garnet solid electrolyte ceramic sheet is polished smooth with sandpaper, and then gold is sprayed on both sides of the ceramic sheet using a gold spraying instrument as an ion blocking electrode. The AC impedance test is performed using Metrohm Autolab, with an AC voltage of 10mV and a frequency of 1-10MHz. The AC impedance of the ceramic sheet is thus obtained. The ionic conductivity is calculated by the formula σ=L / RS, where L is the thickness of the ceramic sheet, R is the AC impedance of the ceramic sheet, and S is the single-sided area of the ceramic sheet.
[0070] In the present invention, the density of the solid electrolyte ceramic sheet is calculated by the following formula: density (%) = (measured density / theoretical density) × 100%, wherein the theoretical density is calculated by the unit cell parameters, and the measured density is measured by the water displacement method. The specific method of the water displacement method is: first use a balance to measure the mass m of the object, then put an appropriate amount of water in a measuring cylinder, read the volume number V1 of the water at this time, tie the object with a thin wire, slowly slide down along the wall of the measuring cylinder until it is completely immersed, read the volume number V2 at this time, and use the density formula to calculate the density of the object: ρ = m / (V2-V1).
[0071] All the above tests were carried out at room temperature.
[0072] The XRD pattern of the solid electrolyte obtained in Example 1 is as follows: Figure 2 As shown; the impedance spectrum is as Figure 3 As shown, the AC impedance of the ceramic sheet is 115 ohms; the SEM picture is as follows Figure 4 As shown; the ionic conductivity and density data are listed in Table 1.
[0073] Example 2 Li 6.5 Ga 0.0667 LqCy 1.85 W 0.15 O 12 Preparation and characterization of
[0074] Li was obtained under the same conditions as in Example 1 except that the dosage of gallium oxide (Ga2O3) and tungsten oxide (WO3) was adjusted so that the doping amounts of Ga and W were adjusted to 0.0667 and 0.15 respectively and the dosage of lithium hydroxide monohydrate (LiOH·H2O) and zirconium oxide (ZrO2) was adjusted accordingly. 6.5 Ga 0.0667 LqCy 1.85 W 0.15 O 12 Ceramic wafers are prepared and characterized.
[0075] Example 3 Li 6.45 Ga 0.05 LqCy 1.8 W 0.2 O 12Preparation and characterization of
[0076] Li was obtained under the same conditions as in Example 1 except that the amounts of lithium hydroxide monohydrate (LiOH·H2O), gallium oxide (Ga2O3) and tungsten oxide (WO3) were adjusted so that the doping amounts of Ga and W were adjusted to 0.05 and 0.2 respectively and the amounts of lithium hydroxide monohydrate (LiOH·H2O) and zirconium oxide (ZrO2) were adjusted accordingly. 6.45 Ga 0.05 LqCy 1.8 W 0.2 O 12 Ceramic wafers are prepared and characterized.
[0077] Example 4 Li 6.6 Ga 0.1 LqCy 1.9 Ta 0.1 O 12 Preparation and characterization of
[0078] Li was obtained under the same conditions as in Example 1 except that W was changed to Ta (the precursor was Ta2O5) and the amount of lithium hydroxide monohydrate (LiOH·H2O) was adjusted. 6.6 Ga 0.1 LqCy 1.9 Ta 0.1 O 12 Ceramic wafers are prepared and characterized.
[0079] Example 5 Li 6.5 Al 0.1 LqCy 1.9 W 0.1 O 12 Preparation and characterization of
[0080] Li was obtained under the same conditions as in Example 1 except that Ga was changed to Al (the precursor was Al2O3). 6.5 Al 0.1 LqCy 1.9 W 0.1 O 12 Ceramic wafers are prepared and characterized.
[0081] Comparative Example 1 Li7La3Zr2O 12 Preparation and characterization of
[0082] Li7La3Zr2O was obtained under the same conditions as in Example 1 except that the doping amounts of Ga and W were reduced to 0 (i.e., no doping was performed) and the amounts of lithium hydroxide monohydrate (LiOH·H2O) and zirconium oxide (ZrO2) were adjusted accordingly. 12 Ceramic wafers are prepared and characterized.
[0083] Comparative Example 2 Li 4.5 Ga 0.1 LqCy 0.9 W 1.1 O 12 Preparation and characterization of
[0084] Li was obtained under the same conditions as in Example 1 except that the doping amount of W was adjusted to 1.1 and the amounts of lithium hydroxide monohydrate (LiOH·H2O) and zirconium oxide (ZrO2) were adjusted accordingly. 4.5 Ga 0.1 LqCy 0.9 W 1.1 O 12 Ceramic wafers are prepared and characterized.
[0085] Comparative Example 3 Li 3.5 Ga 1.1 LqCy 1.9 W 0.1 O 12 Preparation and characterization of
[0086] Li was obtained under the same conditions as in Example 1 except that the Ga doping amount was adjusted to 1.1 and the amount of lithium hydroxide monohydrate (LiOH·H2O) was adjusted accordingly. 3.5 Ga 1.1 LqCy 1.9 W 0.1 O 12 Ceramic wafers are prepared and characterized.
[0087] Comparative Example 4 Li 5.9 Ga 0.3 LqCy 1.9 W 0.1 O 12 Preparation and characterization of
[0088] Li was obtained under the same conditions as in Example 1 except that the Ga doping amount was adjusted to 0.3 and the amount of lithium hydroxide monohydrate (LiOH·H2O) was adjusted accordingly. 5.9 Ga 0.3 LqCy 1.9 W 0.1 O 12 Ceramic wafers are prepared and characterized.
[0089] like Figure 1As shown in the figure, after co-doping with Ga and W, under the same sintering conditions, the size of the ceramic sheet after sintering in Example 1 has shrunk significantly, while the size of the ceramic sheet after sintering in Comparative Example 1 has not changed significantly, indicating that the ceramic sheet of Example 1 forms a low eutectic phase due to co-doping with Ga and W, thereby reducing the sintering temperature. In other words, the sintering temperature of 1100°C is too low for LLZO not doped with Ga and W, and cannot achieve sufficient sintering of the LLZO ceramic sheet.
[0090] like Figure 2 As shown in the figure, it can be found that Example 1 doped with Ga and W exhibits a pure cubic phase structure (compared with PDF card: 45-0109), for example, standard cubic phase XRD peaks are displayed at 17°, 26°, and 37°, without other impurity peaks, indicating that Ga and W co-doping stabilizes the LLZO cubic phase at room temperature; while Comparative Example 1 not doped with Ga and W, at Figure 2 An obvious tetragonal phase peak appears at the middle mark.
[0091] Table 1
[0092]
[0093] Table 1 shows the test results of ionic conductivity and density of the embodiments and comparative examples. Compared with the undoped solid electrolyte obtained in Comparative Example 1, the LLZO solid electrolyte co-doped with Ga and W shown in Table 1 can significantly improve the ionic conductivity and density of the garnet-type solid electrolyte. Due to the B-position doping, the amount of doping elements at the A-position, especially Ga, is reduced, thereby achieving the effect of reducing costs. In addition, as shown in Table 1, when the A-position doping element is changed to Al (Example 5) and the B-position doping element is changed to Ta (Example 4), the ionic conductivity and density of the obtained garnet-type solid electrolyte are still significantly higher than the ionic conductivity of Comparative Example 1.
[0094] In addition, when the doping amounts of the A and B sites are varied within the preferred range of the present invention (Examples 2 and 3), the ionic conductivity and density of the obtained garnet-type solid electrolyte are still maintained at a very high level (greater than 10×10 -4 When the doping amount of the A and B positions is greater than the range of the present invention (Comparative Examples 2 and 3), the ionic conductivity and density of the obtained solid electrolyte are significantly reduced, close to or even lower than the undoped case in Comparative Example 1.
[0095] In addition, according to the ionic conductivity and density data of Comparative Example 4, when the lithium content in the solid electrolyte is 5.9, that is, outside the scope of the present invention, although the ionic conductivity and density of the obtained solid electrolyte are still significantly better than those of other comparative examples, they are still far behind the ionic conductivity of the solid electrolytes of Examples 1 to 5. Therefore, in the present invention, the lithium content in the solid electrolyte is preferably greater than or equal to 6.0.
[0096] Figure 4 The Li in Example 1 is shown 6.5 Ga 0.1 LqCy 1.9 W 0.1 O 12 SEM images of ceramic sheets, such as Figure 4 As shown, the surface of the solid electrolyte after sintering presents a typical structure of pure cubic phase crystals, indicating that the components are fully combined to form a single crystal structure, which is beneficial to the transmission of electrons in the solid electrolyte. In addition, thanks to the co-doping of Ga and W, there are no obvious pores in the solid electrolyte after sintering at a lower temperature, indicating that after doping with Ga and W, the solid electrolyte grains can grow at a lower temperature and connect to each other to form a highly dense ceramic solid electrolyte.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte is represented by Formula 1, Li 7-mx-(n-4)y A x La3Zr 2-y B y O 12 Formula 1 wherein A is one or more elements selected from Ga, Al, and Zn, B is one or more elements selected from W, Ta, Nb, and Sb, 0 < x ≤ 1, 0 < y ≤ 1, and 7 - mx - (n - 4)y ≥ 6, where m is the valence state of A present in the solid electrolyte, being 2 or 3, and n is the valence state of B present in the solid electrolyte, being 5 or 6.
2. The solid electrolyte according to claim 1, characterized in that In Formula 1, A is Ga or Al, and m is 3; and / or, B is W or Ta, and n is 5 or 6.
3. The solid electrolyte according to claim 1 or 2, characterized in that In Formula 1, A is Ga, and m is 3; and / or, B is W, and n is 6; and / or, 0.02 ≤ x ≤ 1, preferably 0.02 ≤ x ≤ 0.2; and / or, 0.02 ≤ y ≤ 1, preferably 0.02 ≤ y ≤ 0.
2.
4. A method for preparing a solid electrolyte according to any one of claims 1 to 3, characterized in that: The preparation method includes the following steps: (1) Mix the precursors of each element with a solvent, then perform ball milling treatment, and then dry; (2) Pre-burn the mixture obtained in step (1), then mix it with the solvent again, perform ball milling treatment, and then dry; (3) Mold the mixture obtained in step (2); (4) Sinter the molded body obtained in step (3) to obtain a solid electrolyte.
5. The preparation method according to claim 4, characterized in that: In step (1), the molar content of the lithium source is 5% to 20% in excess relative to the lithium element in the solid electrolyte, preferably 10% to 15%.
6. The preparation method according to claim 4, characterized in that: In step (2), the pre-burning temperature is 700 to 1100 °C, preferably 750 to 900 °C.
7. The preparation method according to claim 4, characterized in that: In step (3), molding is performed by cold pressing.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (4), the sintering temperature is 1000 to 1500 °C, preferably 1000 to 1200 °C, more preferably 1050 to 1150 °C.
9. Application of the solid electrolyte according to any one of claims 1 to 3 or the solid electrolyte obtained by the preparation method according to any one of claims 4 to 8 in a solid-state lithium-ion battery.
10. A solid-state lithium-ion battery, which includes the solid electrolyte according to any one of claims 1 to 3 or the solid electrolyte obtained by the preparation method according to any one of claims 4 to 8.
Citation Information
Cited By
Al-Nb co-doped lithium lanthanum zirconium oxide, preparation method thereof and lithium ion battery
CN120057983A